2019
DOI: 10.1002/jcp.29308
|View full text |Cite
|
Sign up to set email alerts
|

MKP1 reduces neuroinflammation via inhibiting endoplasmic reticulum stress and mitochondrial dysfunction

Abstract: MAP kinase phosphatase 1 (MKP1) has been identified as an antiapoptotic protein via sustaining mitochondrial function. However, the role of MKP1 in neuroinflammation has not been fully understood. The aim of this study is to figure out the influence of MKP1 in lipopolysaccharide (LPS)-treated microglia BV-2 cells and investigate whether MKP1 reduces BV-2 cell death via modulating endoplasmic reticulum (ER) stress and mitochondrial dysfunction. The results of this study demonstrated that MKP1 was rapidly downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…ER stress has been demonstrated to be a critical event to cause cerebral IR injury, and recent studies showed extensive involvement of ER stress in microglial activation to participate in diverse cerebral injuries including Alzheimer's Disease [51], spinal cord injury [52] and LPS/cocaine-induced neuroinflammation [17,53]. PTP1B was reported to be a positive regulator of ER stress [15,16], yet its role in microglial ER stress has not been well illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress has been demonstrated to be a critical event to cause cerebral IR injury, and recent studies showed extensive involvement of ER stress in microglial activation to participate in diverse cerebral injuries including Alzheimer's Disease [51], spinal cord injury [52] and LPS/cocaine-induced neuroinflammation [17,53]. PTP1B was reported to be a positive regulator of ER stress [15,16], yet its role in microglial ER stress has not been well illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies. For example, MKP-1 deletion caused mitochondrial damage, resulting in decreased insulin release in obesity [41,61]. In diabetic rats, MKP-1 overexpression improved cardiac performance by promoting mitochondrial metabolism [62].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium signal transduction, lipid transport, and energy metabolism are regulated by mitochondria-ER interactions, although detailed molecular patterns have not been identified [40]. Recent studies have identified mitogen-activated protein kinase (MAPK) phosphatase 1 (MKP-1) as a novel regulator of ER function and mitochondrial homeostasis in neuroinflammation [41] and diabetic nephropathy [42]. In this study, we asked whether MKP-1 affects myocardial postischemia damage through regulating mitochondrial homeostasis and ER function.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the role of PTP1B as a positive regulator of microglial activation, and inhibition or deficiency of PTP1B effectively attenuated neuroinflammation [11,49,50]. ER stress has been demonstrated to be a critical event to cause cerebral IR injury, and recent studies showed extensive involvement of ER stress in microglial activation to participate in diverse cerebral injuries including Alzheimer's Disease [51], spinal cord injury [52] and LPS/cocaine-induced neuroinflammation [17,53]. PTP1B was reported to be a positive regulator of ER stress [15,16], yet its role in microglial ER stress has not been well illustrated.…”
Section: Discussionmentioning
confidence: 99%